BMP9 ameliorates amyloidosis and the cholinergic defect in a mouse model of Alzheimer’s disease - Burke, Rebecca M. (National Academy of Sciences, 2013)
Bone morphogenetic protein 9 (BMP9) promotes the acquisition of the cholinergic phenotype in basal forebrain cholinergic neurons (BFCN) during development and protects these neurons from cholinergic dedifferentiation following axotomy when administered in vivo. A decline in BFCN function occurs in patients with Alzheimer’s disease (AD) and contributes to the AD-associated memory deficits. We infused BMP9 intracerebroventricularly for 7 d in transgenic AD model mice expressing green fluorescent protein specifically in cholinergic neurons (APP.PS1/CHGFP) and in wild-type littermate controls (WT/CHGFP). We used 5-mo-old mice, an age when the AD transgenics display early amyloid deposition and few cholinergic defects, and 10-mo-old mice, by which time these mice exhibit established disease. BMP9 infusion reduced the number of Aβ42-positive amyloid plaques in the hippocampus and cerebral cortex of 5- and 10-mo-old APP.PS1/CHGFP mice and reversed the reductions in choline acetyltransferase protein levels in the hippocampus of 10-mo-old APP.PS1/CHGFP mice. The treatment increased cholinergic fiber density in the hippocampus of both WT/CHGFP and APP.PS1/CHGFP mice at both ages. BMP9 infusion also increased hippocampal levels of neurotrophin 3, insulin-like growth factor 1, and nerve growth factor and of the nerve growth factor receptors, tyrosine kinase receptor A and p75/NGFR, irrespective of the genotype of the mice. These data show that BMP9 administration is effective in reducing the Aβ42 amyloid plaque burden, reversing cholinergic neuron abnormalities, and generating a neurotrophic milieu for BFCN in a mouse model of AD and provide evidence that the BMP9-signaling pathway may constitute a therapeutic target for AD.